Pertimbangan Hakim Dalam Menjatuhkan Sanksi Pidana Penjara Tanpa Rehabilitasi Medis Terhadap Terdakwa Penyalah Guna Narkotika Bagi Diri Sendiri - Adi Bambang Waseso; Edy Herdyanto., S.H., M.H (Sebelas Maret University, 2019)
This research examine issues concerning reason District Court of Kota Agung in deciding verdict against the Defendant of narcotics class one abuser for himself. This research include normative law researchNarcotics is a substance or a drug derived from a plant or not plant, either synthetic or semisynthetic, which can cause a decrease or alteration of consciousness, and can lead to dependence. Actually drug is a substance or drug that can be useful and necessary for the treatment of certain diseases. However, the use of which is not in accordance with the standards for treatment, would cause harm to themselves and society at large the younger generation. Thus the drug abusers should be rehabilitated. In the Narcotics Act has regulated how the arrangements for the rehabilitation of drug abusers. Abusers can we distinguish again become addicts and victims of drug abusers. Because they both use narcotics without rights and against the law. However, the setting for the abusers impressed overlap. There are criminal sanctions and penalties related actions in a single article abusers. The regulation stipulated in Article 127, where paragraph (1) of the criminal sanctions, while paragraph (2) and (3) of the sanctions measures (rehabilitation).It happened at the District Court Kota Agung No:32/Pid.Sus/2015/PN.Kot, the judge consideration do not consider correctly whole of indictment, evidence and witness statements in article 127 where paragraphThe defendant according to the statements of witnesses, experts, up to more documentary evidence leads to a drug addict, but the panel of Judges prefer imprisonment verdict without rehabilitation. Whereas in the article 127, where paragraph (3) someone who is proven to be a drug abuser must undergo a rehabilitation process.